Potassium catalysts supported on γ-Al2O3 to produce biodiesel - Torres-Aldaco, Alejandro; Torres-Cervantes, Jessica; Lugo-Leyte, Raúl; Lugo-Méndez, Helen (Renewable Energy, Biomass & Sustainability, 2021)
Biodiesel production is carried out through homogeneous catalysis that forms complex reaction mixtures and has high operating costs. The aim of this work is to synthesize basic, active and selective heterogeneous catalysts for the transesterification reaction with vegetable oils employing g-alumina as support and potassium as active species. The catalysts were characterized by X-ray diffraction and infrared spectroscopy. The amount of catalyst used in the reaction was scanned in a range of 1-10% w, obtaining a maximum conversion of 85% at 55 °C with 6.5% w/w of catalyst with respect to the reagent load and with a methanol-oil molar ratio of 6: 1, reaching equilibrium conversion at six hours. The catalysts were tested at 40, 45, 50 and 55 °C in the transesterification reaction using refined sunflower oil and anhydrous methanol as reagents in a 6: 1 ratio. The 40% K catalyst obtained the best conversion at 55 °C with 85% and showed a selectivity of 45%.